Mendekonstruksi Etika Jurnalistik di Tengah Disinformasi: Pemberitaan Hoaks di Media Indonesia - Miftakhudin, Miftakhudin (Universitas Prof. Dr. Moestopo (Beragama), 2025)
The rapid growth of online media in Indonesia has reshaped information access but heightened exposure to hoaxes and disinformation. This study examines how hoax reporting is produced and to what extent journalistic ethics such as accuracy, independence, and fairness are upheld in digital newsrooms. Using a qualitative design that combines case study and content analysis, we review documentary materials and conduct in-depth interviews with journalists and media practitioners. Textual deconstruction is applied to identify bias, framing, and implicit messages in hoax-related stories. Findings show that economic pressures, inter-media competition, and the premium on speed frequently shape editorial choices, resulting in weakened verification and occasional departures from ethical norms. These practices erode media credibility and exacerbate public confusion. The study underscores the need for consistent ethical governance, stronger verification protocols, and programs that build critical news literacy. The results inform the development of responsible editorial strategies and provide a reference for communication and media studies on hoax dynamics in Indonesia.